Determination of iron. - Abd. Shukor, Mohd. Yunus; Ahmat Raslan, Shahizal Rizwan; Syed, Mohd Arif; Shamaan, Nor Aripin (2009)

(untitled)
A safe and novel iron determination regent is disclosed wherein said reagent consist of phosphomolybdate species. Also disclosed is a method for preparing phosphomolybdate reagent for spectrophotomeric determination of iron comprising the steps: a. preparing a stock solution of phosphomolybdate in distilled water, said stock solution having a concentrated of 5mM to 100mM; b. adjusting the pH of the phosphomolybdate stock solution in step (a) to a pH between pH 4.0 to 6.0; c. adding a volume of iron stock solution to a volume of the phosphomolybdate solution perpared in step (b); d. adjusting the volume of mixture in step (c) using deionized water; e. leaving the mixture to stand at room temperature for 2 to 60 minutes f. correlating the absorbence of the mixture against control sample.